Assessing college students' sustainability literacy: the development, use, and analysis of an assessment tool - Harmon, Renée, author; Makela, Carole, advisor; Kaiser, Leann, committee member; Switzer, Jamie, committee member; Wallner, Barbara, committee member (Colorado State University. Libraries, 2017)
This dissertation discusses the development, use, and analysis of a knowledge-based multiple-choice sustainability literacy assessment tool used in Spring 2016 at Colorado State University (CSU). CSU is a leading institution of sustainability education and research, and a participant of the Sustainability Tracking, Assessment, and Rating System (STARS). A component of STARS includes assessing college students' sustainability literacy. The study, and the sustainability literacy assessment tool described, were designed within the framework of the Triple Bottom Line (TBL). Data sets were collected and analyzed from a sustainability literacy assessment given in Spring 2016. Findings from the study show students performed highest in environmental sustainability literacy and lowest in social sustainability literacy, two of three dimensions of the TBL. Additionally, four focus groups of students were held at CSU in Spring 2017. The focus groups informed the study of how students' defined the concept of sustainability and the three dimensions of the TBL. Findings from the focus groups indicated the design of the assessment tool did not garner meaningful results. The assessment tool was designed with knowledge-based multiple-choice questions, which did not accurately assess sustainability literacy, according to its definition. Recommendations for redesigning the assessment tool include designing questions that assess students' ability to apply systems-thinking and conduct critical thinking and problem-solving. Sustainability educators should seek to encourage transformational learning when teaching sustainability education. With the recommendations for assessment redesign, the researcher also includes suggestions of unique ways institutions of higher education can assess students' sustainability literacy.
Keywords: institutions of higher education; sustainability literacy; concept of sustainability; triple bottom line; sustainability education